Immunological mechanisms involved in the human response to a dog dander allergoid. (May 2022) - Calzada, D.; Aranda, T.; M Gallego, G.; Escutia, M.R.; Balsa, D.; Álvarez, J.; Mayorga, C.; Salas, M.; Odena, M.A.; Oliveira, E.; Pascal, M.; Carnés, J.
Abstract: Background: Dog allergens are a common cause of allergic sensitisation and trigger respiratory symptoms worldwide. However, clinical evidence regarding dog immunotherapy is limited. Therefore, the aim of this study was to analyse the immunomodulatory properties of a new allergoid from dog dander, thereby deepening the understanding of the molecular mechanisms involved in the reestablishment of the tolerogenic response. Methods: Three independent batches of dog dander native and allergoid allergen extracts were manufactured and characterised. Allergenic profiles were analysed by the identification of all dog allergens and quantification of the major allergens Can f 1 and Can f 5. The allergenicity profile of the allergoid was studied using biological potency and basophil activation tests. In vitro immunomodulatory parameters was evaluated as the capacity of the allergoid to induce IgG antibodies that block IgE binding to the allergen and cytokine promotion (IFN-γ, IL-4, IL-6, IL-10, IL-13, and TNF-α) in PBMCs from allergic donors. Results: The presence of all dog allergens, including Can f 1 and Can f 5, was confirmed in both types of extracts. The new allergoid showed a low IgE binding capacity, which significantly affected the activation of effector cells, such as basophils. The IgG antibodies induced by the allergoid in rabbits blocked human IgE binding epitopes on the dog native extract and induced Th1 and Treg responses by increasing IFN-γ and IL-10 levels in PBMCs from allergic donors. Conclusion: This new dog dander allergoid containing Can f 1 and Can f 5 showed a low capacity to bind IgE and to activate basophils in dog allergic patients. Furthermore, it showed potent activation of Th1 mediators and induction of tolerance through Treg activation. This allergoid could offer a safer profile than the native extract and could be an effective immunotherapy treatment for dog allergic patients. Highlights: The allergen profile and in vitro safety of a new dog dander allergoid is assessed. The dog dander allergoid modulates the allergic response by inducing the secretion of regulatory cytokines. This allergoid could be an effective immunotherapy treatment for dog allergic patients.